PENGARUH PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - Damayanti, Ni Putu Deshinta; Dana, I Made (E-Jurnal Manajemen; Vol 6 No 10 (2017), 2017)
The purpose of this study is to determine the effect of Company Size, Profitability, and Business Risk on Capital Structure in Manufacturing Companies In Indonesia Stock Exchange Period 2013-2015. The population in this study are all manufacturing companies in Indonesia Stock Exchange which amounts to 150 companies. The technique of determining the sample used is purposive sampling, so the final sample is 40 manufacturing companies in Indonesia Stock Exchange. Data collection method used is non participant observation .. This study used multiple linear regression analysis techniques with the help of SPSS 22 for windows applications. Based on the results of the analysis shows that: 1) Company size has a positive and significant effect on the capital structure of the company in Indonesia Stock Exchange, 2) Profitability and Risk has a negative and insignificant effect on the capital structure at manufacturing company in Stock Exchange